Elucidating the Lipid-lowering Mechanism of 6-Gingerol: A Molecular Docking Study Targeting HMG-CoA Reductase, PPAR-α, and CETP - Bao Ngoc, Nguyen; Thi Duong, Trinh; Thanh Tung, Bui (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 4, 2025)
Abstract: Hyperlipidemia is a major risk factor for atherosclerosis and contributes to the growing global burden of cardiovascular diseases, myocardial infarction, and metabolic syndrome. 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMG-CoA reductase), Peroxisome proliferator-activated receptor alpha (PPAR-α), and Cholesteryl Ester Transfer Protein (CETP) are the important determinants of hyperlipidemia by regulating a plethora of transcriptional factors in metabolically active tissues such as adipose tissue, liver, and skeletal muscle. The present study aimed to evaluate the binding affinity of 6-Gingerol ((S)-5-hydroxy-1-(4-hydroxy-3-methoxyphenyl)-3-decanone) with therapeutic target proteins of hyperlipidemia using an in silico approach. The in silico docking studies were performed between 6-Gingerol (PubChem CID: 442793) and HMG-CoA reductase, PPAR-α, and CETP with PDB IDs of 1HW9, 6KXX, and 2OBD, respectively, by using AutoDock Tools 1.5.6. Our results revealed that 6-Gingerol exhibited maximum binding affinities with PPAR-α (-7.2), followed by HMG-CoA reductase (-6.2) and CETP (-6.1) kcal/mol. The docking validation showed RMSD values below 1.5 Å, confirming the reliability and reproducibility of the docking protocol. Furthermore, 6-gingerol satisfied all of Lipinski’s rule of five criteria, exhibited favorable ADMET characteristics, and showed negligible toxicity in silico . Therefore, the 6-gingerol compound shows potential as a multi-target lipid-lowering candidate. Keywords: 6-Gingerol, HMG-CoA reductase, Peroxisome proliferator-activated receptor alpha (PPAR-α), Cholesteryl Ester Transfer Protein, Lipid-Lowering Mechanism.